Bacteriorhodopsin Is a Powerful Light-Driven Proton Pump - Kouyama, Tsutomu (1987)
The activity of bacteriorhodopsin was investigated with Halobacterium halobium cell envelopes, which lack cytoplasmic constituents. It was found that the physiological concentration of magnesium ion greatly enhanced the light-induced pH change; under optimal conditions, the pH change of the external medium was as large as 3.5 pH units, even though the volume fraction of the envelope vesicles was as low as 0.01. This pH change is about three times larger than the largest change reported thus far. This same effect was observed with transition metal ions, but not with other alkaline divalent cations. That is, divalent cations that formed hydroxides below pH 10 were effective in enhancing the light-induced pH change. This result suggests that some divalent cations acted as buffers against a large increase in the internal pH, and that the internal pH was an important factor in determining the activity of bacteriorhodopsin. It was also shown that a high level of the proton-pump activity was maintained in a wide range of external pHs, at least between 4.5 and 9.4.